Alteration of the Retinoid Acid-CBP Signaling Pathway in Neural Crest Induction Contributes to Enteric Nervous System Disorder - Li, Cheng; Hu, Rong; Hou, Nali; Wang, Yi; Wang, Zhili; Yang, Ting; Gu, Yan; He, Mulan; Shi, Yu; Chen, Jie; Song, Weihong; Li, Tingyu (Frontiers in Pediatrics, 2018)
Hirschsprung Disease (HSCR) and/or hypoganglionosis are common pediatric disorders that arise from developmental deficiencies of enteric neural crest cells (ENCCs). Retinoid acid (RA) signaling has been shown to affect neural crest (NC) development. However, the mechanisms underlying RA deficiency-induced HSCR or hypoganglionosis are not well-defined. In this report, we found that in HSCR patient bowels, the RA nuclear receptor RARα and its interacting coregulator CREB-binding protein (CBP) were expressed in enteric neural plexuses in the normal ganglionic segment. However, the expression of these two genes was significantly inhibited in the pathological aganglionic segment. In a Xenopus laevis animal model, endogenous RARα interacted with CBP and was expressed in NC territory. Morpholino-mediated knockdown of RARα blocked expression of the neural crest marker genes Sox10 and FoxD3 and inhibited NC induction. The morphant embryos exhibited reduced nervous cells in the gastrointestinal anlage, a typical enteric nervous deficiency-associated phenotype. Injection of CBP mRNA rescued NC induction and reduced hypoganglionosis-associated phenotypes. Our work demonstrates that RARα regulates Sox10 expression via CBP during neural crest induction, and alteration of the RA-CBP signaling pathway may contribute to the development of enteric nervous system disorders.